A comparative systematic review and meta-analysis on the diagnostic accuracy of non-invasive tests for Helicobacter pylori detection in elderly patients - Omar, Mahmud; Abu-Salah, Razi; Agbareia, Reem; Sharif, Yusra; Levin, Roni; Lahat, Adi; Sharif, Kassem (Frontiers in Medicine, 2023)
Background: Helicobacter pylori (H. pylori) infection, a type I carcinogen, affects approximately 50% of the global population, correlating with various gastric pathologies.Notably, diagnostic sensitivities of non-invasive methods, such as the stool antigen test (HpSA), Serology, and Urea Breath Test (UBT), have been suggested to be less effective in older age groups. This study systematically reviews and meta-analyzes the diagnostic accuracy of these tests within the elderly population.Methods: A comprehensive literature search was performed across multiple databases, including PubMed, Medline, and Web of Science, up to July 2023. Data were pooled and analyzed using random-effects models. Sensitivity, specificity, and Diagnostic Odds Ratios (DOR) were computed for the tests. Heterogeneity and risk of bias were assessed.Results: Eight studies involving diverse geographic locations and totaling between 46 and 1,441 participants per study were included. The pooled sensitivity and specificity for HpSA were 72.5% and 94.7%, for Serology 83.7% and 73.3%, and for UBT 96.4% and 88.3%, respectively. DOR for UBT, HpSA, and Serology were 94.5, 47.9, and 14.2, respectively. High levels of heterogeneity were observed across the studies.UBT and HpSA proved effective for diagnosing H. pylori in those over 60, while serology showed lower specificity. Despite methodological variations in available studies, these non-invasive tests offer reliable alternatives, especially for older patients who recently undergone endoscopy or without an indication for it, warranting consideration by healthcare practitioners.